An in vivo evaluation of bone response to three implant surfaces using a rabbit intramedullary rod model - Hermida, Juan C (BioMed Central, 2010)
Our study was designed to evaluate osseointegration among implants with three surface treatments: plasma-sprayed titanium (P), plasma-sprayed titanium with hydroxyapatite (PHA), and chemical-textured titanium with hydroxyapatite (CHA). Average surface roughness (Ra) was 27 microns for the P group, 17 microns for the PHA group, and 26 microns for the CHA group. Bilateral distal intramedullary implants were placed in the femora of thirty rabbits. Histomorphometry of scanning electron microscopy images was used to analyze the amount of bone around the implants at 6 and 12 weeks after implantation. Greater amounts of osseointegration were observed in the hydroxyapatite-coated groups than in the noncoated group. For all implant surfaces, osseointegration was greater at the diaphyseal level compared to the metaphyseal level. No significant differences were seen in osseointegration between the 6 and 12 week time points. Although the average surface roughness of the P and the CHA groups was similar, osseointegration of the CHA implants was significantly greater. The results of this in vivo lapine study suggest that the presence of an hydroxyapatite coating enhances osseointegration despite similarities in average surface roughness.